MEANINGS AND IMAGES ON THE POLITICAL DISCOURSE OF LIBERALISM AND CONSERVATISM IN LIBERAL COSTA RICA (1889-1914) - Gómez Solano, Juan Alberto (2022)
The article presents the set of meanings and social representations that were formed around the discussion of the liberal-conservative concepts for the Costa Rican case, during the twilight of the nineteenth century and the early twentieth century, which were marked by a convulsive and unequal political-electoral and sociocultural environment within Costa Rican society. This was due to tensions that arose between liberals and conservative popular sectors that were supported by the Catholic Church. The first part of the text develops a brief overview of the theoretical origins of both notions and their evolution over time during the 19th century in the Costa Rican case. Subsequently, it delves into the scope of the liberal-conservative discussion in the late nineteenth century and the dawn of the twentieth century.